Modification of meta-iodobenzylguanidine uptake in neuroblastoma cells by elevated temperature. - Armour, A. (Nature Publishing Group, 1994)
Successful imaging or treatment of neuroblastoma with 131I-meta-iodobenzylguanidine (131I-mIBG) depends on the selectivity of active (type 1) uptake of mIBG in neuroblastoma cells relative to passive (type 2) uptake present in most normal tissues. This study investigates the effects of moderately elevated temperature (39-41 degrees C) on the cellular uptake of 131I-mIBG in two neuroblastoma cell lines [SK-N-BE(2c) and IMR-32] and in a non-neuronal (ovarian carcinoma) cell line (A2780). In SK-N-BE(2c), a cell line with high active uptake capacity, the specific (type 1) uptake was reduced by 75% (P < 0.001) at 39 degrees C. Both IMR-32 and A2780 have a low capacity for accumulation of mIBG by active uptake. These cell lines demonstrated a statistically significant increase in accumulation at 39 degrees C, mainly as a result of increased non-specific transport. At 41 degrees C uptake of 131I-mIBG was reduced in all cell lines. Thus, the active component of mIBG uptake is more vulnerable to increased temperature than the passive component. It seems probable that moderately increased temperature will have an unfavourable effect on the therapeutic differential for targeted radiotherapy of neuroblastoma using radiolabelled mIBG.